The Effect of Once-Daily Gabapentin Extended Release Formulation in Patients With Postamputation Pain - Nebojsa Nick Knezevic; Nebojsa Nick Knezevic; Nebojsa Nick Knezevic; Tabish Aijaz; Kenneth D. Candido; Kenneth D. Candido; Kenneth D. Candido; Svetlana Kovaleva; Alexei Lissounov; Ivana Knezevic (Frontiers Media S.A., 2019)
ObjectivesTo compare gabapentin extended-release, a gastro-retentive formulation, in relieving postamputation pain among gabapentin-experienced and gabapentin-naïve patients.DesignOpen-labeled pilot study.SubjectsSixteen patients with postamputation pain (8 patients in the gabapentin-experienced and 8 patients in the gabapentin-naïve groups).MethodsPatients were started on gabapentin extended-release and were followed up for 8 weeks. Patients reported their pain severity during rest and movement using a numeric rating scale (NRS), interference of pain with daily activities using the modified brief pain inventory (MBPI) questionnaire, and treatment satisfaction using the treatment satisfaction questionnaire for medication (TSQM).ResultsPatients from both gabapentin-experienced and gabapentin-naïve groups achieved a significant and sustainable pain relief over the course of therapy. The pain scores at rest decreased in both gabapentin-experienced and gabapentin-naïve groups from 5.88 ± 1.36 and 4.88 ± 2.95 to 1.88 ± 0.99 and 1.38 ± 1.51, respectively. An average percent of pain relief with gabapentin extended-release was noted to be significant (p < 0.01) after 8 weeks of therapy among gabapentin-experienced (81.25 ± 16.42%) and gabapentin-naïve groups (85 ± 17.73%) when compared to baseline for gabapentin-experienced (31.25 ± 29%) and gabapentin-naïve groups (36.25 ± 34.2%), respectively. Gabapentin-experienced and gabapentin-naïve groups had no significant difference in global satisfaction from treatment (79.14 ± 10.47 and 83.3 ± 20.82), convenience of treatment (73.78 ± 19.04 and 90.44 ± 11.66), effectiveness of treatment (72.6 ± 10.1 and 79.73 ± 11.6). The only statistically significant difference among gabapentin-experienced and gabapentin-naïve groups was found in adverse event tolerability (65.78 ± 10.36 and 85.8 ± 10.14, p < 0.01).ConclusionOnce-daily dosing of gabapentin-extended release showed significant improvement in pain severity and functional status, with no difference found between gabapentin-experienced versus gabapentin-naïve patients.